Pemanfaatan Metode Moving Average dalam Menentukan Awal Waktu Salat Subuh Menggunakan Sky Quality Meter (SQM) - Abu Yazid Raisal; Yudhiakto Pramudya; Okimustava ,; Muchlas , (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2019)
The beginning of prayer time is important for Muslims because Islam advocates for prayer at the beginning of time. The beginning of Zuhr, Asar and Maghrib prayer times can be done by looking position of the Sun directly. However, the position of the sun cannot be directly observed to determine the beginning of the Fajr and Isha prayer times, because the Sun is below the horizon. The beginning of the Fajr prayer time can be determined by measuring sky brightness using the Sky Quality Meter (SQM). Many factors can affect SQM in collecting light so that the data is not separated from noise. The use of the moving average method reduces noise, making it easier to determine the beginning of the Fajr prayer time using SQM.